Przyszłość nauk humanistycznych w perspektywie metafilozoficznej - Cyprian Gawlik, Cyprian Gawlik (Człowiek i Społeczeństwo, 2020)
The purpose of this paper is to ponder upon the future of the humanities from a metaphilosophical perspective inspired by G.W.F. Hegel’s philosophy of the history of philosophy. The need for this reflection follows from the crisis that the humanities are facing today due to global changes in higher education, caused by the domination of the capitalist economy and the dramatic development of technology. The author assumes that the essence of the humanities is determined by the formation of self-understanding (Bildung) and proposes to consider this issue from a broader historical point of view and apart from the institutional context of human sciences, namely in the light of the history of philosophy, understood according to the Hegelian approach as the development of selfknowledge. The paper extensively discusses Hegel’s philosophy of the history of philosophy, as well as subsequent metaphilosophical positions inspired by Hegel’s thought (especially that of August Cieszkowski and Martin Heidegger). As a result, the question about the future of the humanities is transformed into a postulate of reflection on the primacy of technoscientific thinking in the modern world. In line with the Hegelian view of knowledge development – attributing autoperformative function to self-cognition – this kind of reflection is a potential remedy for the crisis currently diagnosed in the humanities.